Selling with evidence - Frédéric Koessler; Basilike Skreta (Theoretical Economics, 2019)
We study the informed-principal problem in a bilateral asymmetric information trading setting with interdependent values and quasi-linear utilities. The informed seller proposes a mechanism and voluntarily certifies information about the good's characteristics. When the set of certifiable statements is sufficiently rich, we show that there is an ex-ante profit-maximizing selling procedure that is an equilibrium of the mechanism proposal game. In contrast to posted price settings, the allocation obtained when product characteristics are commonly known (the unravelling outcome) may not be an equilibrium allocation, even when all buyer types agree on the ranking of product quality. Our analysis relies on the concept of strong Pareto optimal allocation, originally introduced by Maskin and Tirole (1990) in private value environments.
Keywords: C72; D82; 330; Informed principal; consumer heterogeneity; interdependent valuations; product information disclosure; mechanism design; certification